THE IMPACT OF LITERACY ON FINANCIAL SATISFACTION: A STUDY OF MILLENNIAL SHOPEEPAY USERS IN SURAKARTA, INDONESIA - Amelia Febriyanti; Darmanto Darmanto; Hadi Samanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to investigate the influence of financial satisfaction based on financial literacy on ShopeePay fintech users among the millennial generation. Data collection was carried out through questionnaires. The population in this research is all millennial generations in the city of Surakarta who use ShopeePay fintech facilities with a research sample of 100 respondents. Data analysis used Multiple Linear Regression Analysis with SPSS version 23.0 software. The results of this research show that financial literacy has a significant influence on financial satisfaction, which in turn influences behavior and attitudes towards using ShopeePay fintech.